Factors related to the parallel use of complementary and alternative medicine with conventional medicine among patients with chronic conditions in South Korea - Choi, Byunghee; Han, Dongwoon; Na, Seonsam; Lim, Byungmook (Integrative medicine research, 2017)
This study aims to examine the characteristics and behavioral patterns of patients with chronic conditions behind their parallel use of the conventional medicine (CM) and the complementary and alternative medicine (CAM) that includes traditional Korean Medicine (KM). This cross-sectional study used the self-administered anonymous survey method to obtain the results from inpatients who were staying in three hospitals in Gyeongnam province in Korea. Of the 423 participants surveyed, 334 participants (79.0%) used some form of CAM among which KM therapies were the most common modalities. The results of a logistic regression analysis showed that the parallel use pattern was most apparent in the groups aged over 40. Patients with hypertension or joint diseases were seen to have higher propensity to show the parallel use patterns, whereas patients with diabetes were not. In addition, many sociodemographic and health-related characteristics are related to the patterns of the parallel use of CAM and CM. In the rural area of Korea, most inpatients who used CM for the management of chronic conditions used CAM in parallel. KM was the most common in CAM modalities, and the aspect of parallel use varied according to the disease conditions.